Rancang Bangun Sistem Manajemen Pemeriksaan Tiket Penumpang Kereta Api Otomatis Menggunakan RFID - Dikri Nur ahkam (Jurnal Jaringan Telekomunikasi, 2019)
Currently, public transportation is needed by Indonesian people to meet human needs for increased movement or mobility. Along with the increasing public interest in trains demanding an increase in services such as the checking system for passenger tickets still using manual system by officers by approaching passengers in each car. This is'nt efficient, so an automatic passenger ticket inspection system using RFID is required. Passenger RFID is scanned when check-in at station then the data is sent to server via nodeMCU ESP8266, the officer only checks passengers through the data display on the monitor. This system also has a Flex sensor in each seat which functions to detect seats that aren't purchased but are occupied by other passengers.The test results concluded that the reading of the RFID card against RFID reader reached distance and barrier with a thickness of 3cm, the DHT11 temperature sensor showed reading accuracy up to 96.6%, and the voltage on the flex sensor on seat 1 had average load of 2.6V, seat 2 average 2.82V, seat 3 averaged 2.84V, seat 4 averaged 2.67V, while the voltage on the flex sensor in seat 1 had an average load of 2.38V, seat 2 averaged 2.29V , seat 3 averages 2.65V, seat 4 averages 2.60V. The value of the flex sensor tension in each condition isn't the same for each seat because the surface shape and thickness of each chair are different. All systems can run properly, starting from sensor readings, transmitting data and displaying data on web.